Penerapan Teknologi Digital dalam Transaksi Keuangan pada PT Bank Negara Indonesia (Persero) Tbk: Penelitian - Nabilah Firyal Basyasyah; Theodorus Sendjaja (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The development of digital technology is a challenge in the banking industry in Indonesia. PT Bank Negara Indonesia (Persero) Tbk is one of the banks that has implemented various digital innovations in its financial transactions in order to face increasingly competitive challenges in the banking industry and increase the efficiency, speed, and convenience of financial transaction services. This study aims to analyze the effectiveness of the application of digital technology in financial transactions at PT Bank Negara Indonesia (Persero) Tbk (BNI). The research method uses a qualitative descriptive approach based on literature studies from official reports and scientific publications. The results show that digital applications such as Wondr and BNIDirect have succeeded in increasing transaction volume by 52% and reducing operational costs by more than 90%. Digitalization also increases the speed and convenience of services. However, BNI still faces obstacles such as cybersecurity risks and low digital literacy. The conclusion of the study shows that digital transformation at BNI is effective, but needs to be balanced with strengthening the supporting ecosystem to be more inclusive and sustainable.